Effects of the cAMP-elevating agents cilostamide, cilostazol and forskolin on the phosphorylation of Akt and GSK-3β in platelets - Hayashi, Hideki; Sudo, Toshiki (Thrombosis and Haemostasis, 2009)
Elevating intracellular cAMP has been shown to inhibit platelet function. cAMP interferes with platelet-activating signals which lead to aggregation inhibition, but the precise mechanism is unclear.The present study examined if cAMP-elevating agents inhibited phosphatidylinositol 3-kinase (PI3-kinase) signaling in rat platelets by immunoblotting. Akt is one of the key molecules downstream of PI3K, and is phosphorylated by collagen stimulation. The phosphodiesterase-3 (PDE3) inhibitors cilostamide and cilostazol, and the adenylate cyclase activator forskolin, inhibited collagen-induced Akt phosphorylation at Ser473.The inhibitory effects of these cAMP-elevating agents on Akt phosphorylation were unchanged in the presence of the PKA (cyclic AMP-dependent protein kinase) inhibitor H-89. These effects were consistent with inhibition of platelet aggregation. It is known that inhibition of Akt phosphorylation leads to inhibition of phosphorylation of glycogen synthase kinase 3-beta (GSK-3β), which is an effector of Akt, but cAMP-elevating agents stimulated GSK-3βphosphorylation at Ser9.The PKA inhibitor H-89 attenuated GSK-3βphosphorylation.The cAMP-elevating agents cilostamide, cilostazol and forskolin did not directly affect the enzyme activity of PI3-kinase.These results suggested that cAMP-elevating agents have two effects on PI3K signalling: inhibition of Akt phosphorylation independent of PKA; and stimulation of GSK-3β phosphorylation dependent on PKA. Our results provide new insights into the inhibitory effect of cAMPelevating agents on platelet function.
Keywords: Akt; cAMP; GSK; phosphorylation; platelet aggregation